Sirolimus Therapy to Halt the Progression of ADPKD - Perico, Norberto (American Society of Nephrology, 2010)
Activation of mammalian target of rapamycin (mTOR) pathways may contribute to uncontrolled cell proliferation and secondary cyst growth in patients with autosomal dominant polycystic kidney disease (ADPKD). To assess the effects of mTOR inhibition on disease progression, we performed a randomized, crossover study (The SIRENA Study) comparing a 6-month treatment with sirolimus or conventional therapy alone on the growth of kidney volume and its compartments in 21 patients with ADPKD and GFR ≥40 ml/min per 1.73 m(2). In 10 of the 15 patients who completed the study, aphthous stomatitis complicated sirolimus treatment but was effectively controlled by topical therapy. Compared with pretreatment, posttreatment mean total kidney volume increased less on sirolimus (46 ± 81 ml; P = 0.047) than on conventional therapy (70 ± 72 ml; P = 0.002), but we did not detect a difference between the two treatments (P = 0.45). Cyst volume was stable on sirolimus and increased by 55 ± 75 ml (P = 0.013) on conventional therapy, whereas parenchymal volume increased by 26 ± 30 ml (P = 0.005) on sirolimus and was stable on conventional therapy. Percentage changes in cyst and parenchyma volumes were significantly different between the two treatment periods. Sirolimus had no appreciable effects on intermediate volume and GFR. Albuminuria and proteinuria marginally but significantly increased during sirolimus treatment. In summary, sirolimus halted cyst growth and increased parenchymal volume in patients with ADPKD. Whether these effects translate into improved long-term outcomes requires further investigation.